Strategi Pengembangan Pantai Wediombo Kabupaten Gunungkidul - Citra Unik Mayasari - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2017)
Abstract - Wediombo beach located in the village Jepitu Girisubo District of Gunung Kidul Regency. Wediombo beach is one of the beaches are very promising, but until now the beach Wediombo not managed properly. The study was conducted through qualitative research by collecting data through interviews, observation, documentation, and secondary data sources in order to know how the influence of internal and external environment as well as strategy development Wediombo Beach Wediombo Beach The result of research the power of aspect originality, uniqueness, variatif, totally, scarcity, wholesomeness. While the weak is from the human resources who don’t have tourism skill yet, capital constraints, facifacilities and infrastructure are inadequate and promotion is not maximized. The external factor to be the threat is competitor and environmental damage caused by lack of awareness of the public and tourists. Regulation , investors , government support into an opportunity in the development Wediombo Beach . Coastal development strategy Wediombo short-term plan : improving the quality of human resources, cooperation with investors, the development of a tourist attraction . Medium-term plan : improvement of infrastructure, promotion , human resource development of tourism. Long-term plan : improved management, regulation, conservation.Keywords : Development Strategy , natural tourism , beachAbstraksi - Pantai Wediombo terletak di Desa Jepitu Kecamatan Girisubo Kabupaten Gunungkidul. Pantai Wediombo ini adalah salah satu pantai yang sangat berpotensi, namun hingga sekarang Pantai Wediombo belum dikelola dengan baik.  Penelitian dilakukan melalui penelitian kualitatif dengan mengumpulkan data melalui wawancara, observasi, dokumentasi, dan sumber data sekunder dengan tujuan mengetahui bagaimana pengaruh lingkungan internal dan eksternal Pantai Wediombo serta strategi pengembangan Pantai Wediombo. Hasil penelitian aspek internal kekuatan berasal dari keaslian, keunikan, keanekaragaman, keutuhan, kemanfaat dan kelangkaan. Adapun faktor kelemahan terjadi pada SDM yang belum sadar wisata, keterbatasan modal, sarana prasarana yang belum memadahi, dan promosi yang belum maksimal. Faktor eksternal yang menjadi ancaman meliputi adanya daya saing dalam wisata yang sejenis dan kerusakan lingkungan akibat kurang kesadaran masyarakat atau wisatawan. Regulasi, investor, dukungan pemerintah menjadi sebuah peluang dalam pengembangan Pantai Wediombo. Strategi pengembangan Pantai Wediombo rencana jangka pendek: peningkatan kualitas SDM, kerjasama dengan investor, pengembangan daya tarik wisata. Strategi jangka menengah: peningkatan sarana dan prasarana, promosi, peningkatan SDM kepariwisataan. Strategi  jangka panjang: peningkatan pengelolaan, regulasi, konservasi. Kata kunci : Strategi Pengembangan, wisata alam, pantai